1232 Trust-Wide Assessment of Delirium in Post-Operative Elective Surgery. (12th October 2021) - Sundar, S; Biggs, S; Abraham, M; Cook, J; Watts, N; Price, R; Brack, M; Brown, N; Dixon, L; Crowther, O; Trenaman, R; Quinn, D; et al.
Abstract: Aim: Delirium is an acute change in cognition and associated with adverse patient outcomes. The incidence of post-operative delirium after elective non-cardiac surgery is unknown. We aimed to assess the incidence of post-operative delirium in this group and the effect on patient outcomes. Method: Patients aged 65 and over who underwent elective non-cardiac surgery were identified on post-operative day three. Delirium screening was performed in real time using the validated 4-AT assessment tool. A retrospective review of the patients' preoperative and perioperative record was conducted to collect demographics and identify risk factors for delirium. Outcome data was collected at 30 days. Patients with a positive delirium score (>4) underwent a more in-depth assessment and managing teams given a delirium management pack. Results: 75 (39 male) consecutive patients were screened over a period of 4 months. Median age 77 years and 18% had frailty assessed as "vulnerable". The majority of patients (37.3%) underwent thoracic surgery, followed by hepatobiliary (17.3%), gynaecological (17.3%), colorectal (12%), maxillofacial (9.3%) and ENT (4%). 5.3% (4) of patients had a positive 4-AT screen. No patients had a formal delirium screen or diagnosis in the initial 48 hours. The median length of stay for patients with a positive screen was 8.5 days (IQR 7.5-12) compared to 8 days (IQR 5-13) for patients with a negative screen. Conclusions: Reassuringly, rate of post-operative delirium following elective operations in our Trust are low (5%). Larger numbers of patients are required to assess the impact this has on patient outcomes and identify correlation with risk factors.